2021
DOI: 10.1177/0011128721999333
|View full text |Cite
|
Sign up to set email alerts
|

Protesting During a Pandemic: Narratives on Risk Taking and Motivation to Participating in the 2020 March on Washington

Abstract: The study elucidates the interplay of COVID-19 and the wave of Black Lives Matter protests to assess motivation and risk taking for protest participation. We draw on protesters’ accounts to examine how police violence influenced the participants decision making to participate in the 2020 March on Washington during a pandemic that exacerbated the risks already in place from protesting the police. We found that protesters’ social position and commitment to the cause provided motivations, along with a zeal to do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…One is that it is at the heart of the United States' current police legitimacy crisis, and is the focal point of contemporary discussions about race and policing. Altruistic fear of the police, for example, appears to explain why many people risked their own lives to attend Black Lives Matter protests during the COVID-19 pandemic-as one protester put it, "if we don't put our bodies on the line, then our children will still be vulnerable to this kind of abuse" (Cobbina et al, 2021(Cobbina et al, , p. 1213. Similarly, as Table 1 shows, it is the language of fear that has dominated public discourse about police-civilian relations in recent years, with prominent figures such as Michelle Obama, LeBron James, Senator Tim Scott, and Pulitzer Prize-winning columnist Eugene Harold 1 Theoretically, the racial gradient reflects Black Americans' longer, more severe history with racial discrimination in the U.S. and the effects of having darker skin color in contemporary American society (Hagan et al, 2005).…”
Section: Why Police-related Fear Is Importantmentioning
confidence: 99%
“…One is that it is at the heart of the United States' current police legitimacy crisis, and is the focal point of contemporary discussions about race and policing. Altruistic fear of the police, for example, appears to explain why many people risked their own lives to attend Black Lives Matter protests during the COVID-19 pandemic-as one protester put it, "if we don't put our bodies on the line, then our children will still be vulnerable to this kind of abuse" (Cobbina et al, 2021(Cobbina et al, , p. 1213. Similarly, as Table 1 shows, it is the language of fear that has dominated public discourse about police-civilian relations in recent years, with prominent figures such as Michelle Obama, LeBron James, Senator Tim Scott, and Pulitzer Prize-winning columnist Eugene Harold 1 Theoretically, the racial gradient reflects Black Americans' longer, more severe history with racial discrimination in the U.S. and the effects of having darker skin color in contemporary American society (Hagan et al, 2005).…”
Section: Why Police-related Fear Is Importantmentioning
confidence: 99%
“…Only household income decrease (H3c) failed to affect participation. The accumulation of grievances resulting from the various protest waves that preceded the 2019 social uprising might have led to a situation similar to that described by Cobbina et al (2021) in which protesting is considered a risk worth taking. Protesting in times of a pandemic can be conceptualized as a new type of high-risk activism, but very different from the one usually theorized in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…In most studies, qualitative methods were applied with an inductive approach which allows research findings to emerge from the frequent, dominant, or significant themes inherent in data, without the restraints imposed by structured methodologies (Thomas, 2006). To identify motivations for Black Lives Matters protest participation amid a global pandemic, Cobbina et al (2021) used an inductive approach to analyze interviews with protesters. They found that activists emphasized the need for justice, pronounced the desire to honor the historic March, and viewed standing up against systemic racism as worth the risk as motivation to mobilize.…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…The remaining nine studies addressed the influence of the pandemic on various specific activism expressions. Four studies investigated activism in favor of the rights of social groups: ethnic minorities (Abidin and Zeng, 2020;Cobbina et al, 2021), immigrants (Zajak et al, 2021), and LGBTQA+ refugees (Holle et al, 2021). Overall, these studies showed how-while the pandemic did not negatively affect the interest and engagement of activists in these social causes, the health concerns and regulatory restrictions associated with traditional, face-to-face forms of protest led to the proliferation of alternative (mainly online) forms of engagement.…”
Section: Impact Of the Pandemic On Pre-established Activist Movementsmentioning
confidence: 99%
See 1 more Smart Citation